Effects of gut microbiota on omega-3-mediated ovary and metabolic benefits in polycystic ovary syndrome mice - Hong Zhang; Lu Zheng; Chuwei Li; Jun Jing; Zhou Li; Shanshan Sun; Tongmin Xue; Kemei Zhang; Mengqi Xue; Chun Cao; Lei Ouyang; Zhang Qian; et al. (BMC, 2023)
Abstract Background Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disorder that frequently exhibits low-grade inflammation, pro-oxidant activity, and gut dysbiosis. PCOS has become one of the leading causes of female infertility worldwide. Recently, omega-3 polyunsaturated fatty acids (PUFAs) have been proven to benefit metabolic disorders in PCOS patients. However, its roles in the regulation of metabolic and endocrinal balances in PCOS pathophysiology are not clear. In the present study, we aimed to explore how omega-3 PUFAs alleviate ovarian dysfunction and insulin resistance in mice with dehydroepiandrosterone (DHEA)-induced PCOS by modulating the gut microbiota. Methods We induced PCOS in female mice by injecting them with DHEA and then treated them with omega-3 PUFAs. 16S ribosomal DNA (rDNA) amplicon sequencing, fecal microbiota transplantation (FMT) and antibiotic treatment were used to evaluate the role of microbiota in the regulation of ovarian functions and insulin resistance (IR) by omega-3 PUFAs. To further investigate the mechanism of gut microbiota on omega-3-mediated ovarian and metabolic protective effects, inflammatory and oxidative stress markers in ovaries and thermogenic markers in subcutaneous and brown adipose tissues were investigated. Results We found that oral supplementation with omega-3 PUFAs ameliorates the PCOS phenotype. 16S rDNA analysis revealed that omega-3 PUFA treatment increased the abundance of beneficial bacteria in the gut, thereby alleviating DHEA-induced gut dysbiosis. Antibiotic treatment and FMT experiments further demonstrated that the mechanisms underlying omega-3 benefits likely involve direct effects on the ovary to inhibit inflammatory cytokines such as IL-1β, TNF-α and IL-18. In addition, the gut microbiota played a key role in the improvement of adipose tissue morphology and function by decreasing multilocular cells and thermogenic markers such as Ucp1, Pgc1a, Cited and Cox8b within the subcutaneous adipose tissues. Conclusion These findings indicate that omega-3 PUFAs ameliorate androgen-induced gut microbiota dysbiosis. The gut microbiota plays a key role in the regulation of omega-3-mediated IR protective effects in polycystic ovary syndrome mice. Moreover, omega-3 PUFA-regulated improvements in the ovarian dysfunction associated with PCOS likely involve direct effects on the ovary to inhibit inflammation. Our findings suggest that omega-3 supplementation may be a promising therapeutic approach for the treatment of PCOS by modulating gut microbiota and alleviating ovarian dysfunction and insulin resistance.